DAMPAK PEMBATASAN MEDIA SOSIAL TERHADAP KECEMASAN DAN KESEJAHTERAAN REMAJA GENERASI ALPHA PADA APLIKASI TIKTOK - Mario Rendy Andreawan; Melvina Firwanda Melati; Azzahra Faradhita Aulia; Ahmad Sukma Andriansyah; Tan Evan Tandiyono (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Digital technology advancement has transformed human lives, especially For Generation Alpha, who have grown up largely influenced by TikTok, developments in digital technology have greatly changed human life. Born between 2010 and 2025, Generation Alpha is the target of this study on how TikTok restrictions influence their mental health and psychological condition. Using a qualitative exploratory descriptive method, thorough interviews and Focus Group Discussions at SMP Negeri 50 Surabaya from March to May 2026 helped to collect information. Five students chosen by means of purposeful sampling made up the first group; the process went on until no fresh data showed up. The interactive model developed by Miles and Huberman helped the data analysis. Though meant to lower anxiety and social pressures, restrictions on social media may unintentionally cause new kinds of psychological problems including digital disconnection, loneliness, and FOMO—Fear of Missing Out—as well as other symptoms. The study points out that any digital regulations should find a compromise between protecting safety and meeting the social needs of those raised in a digital environmen.